TRANSAKSI JUAL BELI ONLINE MELALUI INTERNET (E-COMMERCE) PERSPEKTIF HUKUM ISLAM DI KOTA SAMARINDA - Sapi'i Sapi'i (STAI AL FALAH Banjarbaru, 2019)
The practice of buying and selling online through the internet in the city of Samarinda is the mechanism that sellers offer goods that they sell through social media such as Facebook, Instagram, Twitter, and Whatsapp by looking at the images offered, specifications of goods and their prices. But in this case, not all sellers explain the specifications of the goods and their prices. if the buyer wants the goods offered by the seller then the buyer must pay the funds in advance by transfer, after that the seller will send goods that have been ordered by the buyer, there are problems in buying and selling problems such as dissatisfaction of buyers (consumers) with goods purchased at the order and delays in shipping goods often occur. While in the sale and purchase transaction must be clear and in accordance with the pillars and terms of sale and purchase, and do not contain elements of deception and there is no element of coercion in the sale and purchase. Basically, buying and selling through internet media is permitted, provided the seller must explain the goods they sell in the form of goods specifications, goods prices, delivery times, and matters related to the sale and purchase. Buying and selling via the internet must also not be in conflict with Islamic law, terms and the existence of elements of clarity, and far from the element of deception and no element of coercion and elements of fraud. Buying and selling via the internet in Samarinda city is makruh because buying and selling is permissible but it is not recommended to make this sale because there is more harm than good and there are gharar elements in it, namely the obscurity of the object of buying and selling and its implementation. Keywords: Selling Buy Online, Islamic Law